An Integrated Implementation Framework for an Efficient Transformation to Online Education - Ahmed Al-Hunaiyyan (3696538) (2021)
The least developed countries have been tasked with introducing effective e-learning frameworks as they look to overcome technology inadequacies and lack of research support or vision. Ongoing efforts are reliant upon a mixed-methods approach. A systematic literature analysis and a quantitative examination have been undertaken to achieve a thorough assessment of the available data taken from educational facilities in Kuwait. Results show clear support for embracing e-learning, with most participants recognizing its positives when faced with the scope of challenges its practice may incorporate. Consequently, the authors recommend a framework that is integrated to support a smooth upgrade to online teaching in a manner that furthers the efficacy and understanding of e-learning potential in the context of education in Kuwait and neighboring countries, with a particular focus on how to function during a pandemic lockdown. The proposed framework is structured according to five key tiers: infrastructure, e-learning delivery, LMS, e-Content, and user portal. In support of this, a model of e-Content development is proposed to assist with the establishment and execution of educational materials, in particular, to cope with the lack of digital learning materials in Arabic. Other Information Published in: International Journal of Advanced Computer Science and Applications License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.14569/ijacsa.2021.0120408 Disclaimer: The University of Doha for Science and Technology replaced the now-former College of the North Atlantic-Qatar after an Amiri decision in 2022. UDST has become and first national applied University in Qatar; it is also second national University in the country.